2015
DOI: 10.1038/cddis.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal ceramide generated by acid sphingomyelinase triggers cytosolic cathepsin B-mediated degradation of X-linked inhibitor of apoptosis protein in natural killer/T lymphoma cell apoptosis

Abstract: We previously reported that IL-2 deprivation induced acid sphingomyelinase-mediated (ASM-mediated) ceramide elevation and apoptosis in an NK/T lymphoma cell line KHYG-1. However, the molecular mechanism of ASM–ceramide-mediated apoptosis during IL-2 deprivation is poorly understood. Here, we showed that IL-2 deprivation induces caspase-dependent apoptosis characterized by phosphatidylserine externalization, caspase-8, -9, and -3 cleavage, and degradation of X-linked inhibitor of apoptosis protein (XIAP). IL-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 65 publications
(84 reference statements)
1
51
0
Order By: Relevance
“…However, simultaneous inhibition of both cathepsin B and cathepsin D significantly decreased LCL521-induced cell death (Figure 8A). Western blotting analysis indicated that LCL521 does not alter the levels of cathepsin B and cathepsin D proteins (Figure 8B), suggesting that LCL521 activates the enzymatic activity but not the protein levels of cathepsin B and cathepsin D. Previous studies have shown that ceramide induces xIAP degradation to mediate cell death [44, 46, 48]. Western blotting analysis indicates that although LCL521 treatment decreased xIAP protein level in J774M cells, xIAP protein level is essentially low in J774M cells (Figure 8B), suggesting that xIAP may not play a significant role in MDSCs.…”
Section: Resultsmentioning
confidence: 91%
“…However, simultaneous inhibition of both cathepsin B and cathepsin D significantly decreased LCL521-induced cell death (Figure 8A). Western blotting analysis indicated that LCL521 does not alter the levels of cathepsin B and cathepsin D proteins (Figure 8B), suggesting that LCL521 activates the enzymatic activity but not the protein levels of cathepsin B and cathepsin D. Previous studies have shown that ceramide induces xIAP degradation to mediate cell death [44, 46, 48]. Western blotting analysis indicates that although LCL521 treatment decreased xIAP protein level in J774M cells, xIAP protein level is essentially low in J774M cells (Figure 8B), suggesting that xIAP may not play a significant role in MDSCs.…”
Section: Resultsmentioning
confidence: 91%
“…In another study, aSMase is also proposed as target for cancer therapy since its inhibition induced lysosomal cell death (Aits and Jaattela, 2013). Taniguchi M et al showed that IL-2 deprivation resulted in LaSMase-dependent ceramide generation and caspase-mediated cell death in NK/T lymphoma cells (Taniguchi et al, 2015). Inhibition of aSMase using desipramine, knock-down of aSMase, or inhibition of cathepsin B rescued cells from apoptotic cell death induced by IL-2 deprivation, and proving the role of aSMase in this kind of cell death.…”
Section: Asmase In Pathophysiologymentioning
confidence: 97%
“…Cathepsin D has been linked to the induction of endoplasmatic reticulum stress [50], suppression of autophagy [51], degradation of XIAP [52] and induction of apoptosis [53]. …”
Section: Discussionmentioning
confidence: 99%